HUBUNGAN STATUS GIZI DENGAN KEJADIAN ANEMIA PADA REMAJA PUTRI - Wahyu Putri Handayani; Riri ' Novayelinda; Jumaini ' ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2015)
Abstract This study aim to assesthe relationship of nutritional status with the incidence of anemia among irl adoleccent in SMAN 8 Pekanbaru. This studi used a descriptive research design with cross sectional method. This study conducted on 86 middle girl adolescent in SMAN 8 Pekenbaru using purposive sampling technique. Measuring instrument used in the weight scales, height measurement and hemoglobin multi function monitoring system. The analysis in univariate and bivariate analysis with fisher test. The result showed that there was no relationship between nutritional status and the incidence of anemia in adolescent girl with a significance level of 0.05 was obtained p value < 0.512. It is suggested to the school of to do monitoring the Hb level among student in the school. Keyword: Anemia, young women, nutritional status.